PEMBERDAYAAN KELUARGA MELALUI EDUKASI NUTRISI SEBAGAI UPAYA PENCEGAHAN STUNTING DI DESA TIRTANADI WILAYAH KERJA PUSKESMAS KORLEKO - Fitri Romadonika; Baiq Nurul Hidayati; Syamdarniati Syamdarniati; Raudatul Jannah; Aidatul Fitri (Jurnal LENTERA, 2026)
Stunting remains a chronic nutritional problem and a major public health challenge in Indonesia, including in Tirtanadi Village, within the working area of Korleko Community Health Center, where cases of growth retardation among children are still found due to inadequate nutritional intake. One of the factors contributing to stunting is the limited knowledge of families regarding nutrition and appropriate parenting practices that support child growth and development. This community service activity aimed to improve family knowledge and awareness of the importance of adequate nutrition as an effort to prevent stunting. The method used was family-based nutrition education through health counseling, interactive discussions, and the distribution of educational materials to families with toddlers. The activity involved community health volunteers and local healthcare workers to strengthen participants’ understanding. The results showed an increase in family knowledge regarding balanced nutrition, the selection of nutritious foods, and the importance of the role of all family members in supporting child growth and development. Participants also demonstrated high enthusiasm throughout the activity and were able to explain the educational materials they had received. It can be concluded that family empowerment through nutrition education is an effective strategy for increasing community knowledge and awareness in preventing stunting in Tirtanadi Village.